A hint on the unknown diversity of eastern Andes: high endemicity and new species of mammals revealed through DNA barcoding - Silvia E. Pavan; Edson F. Abreu; Pamela Y. Sánchez-Vendizú; Romina Batista; Roberta A. Murta-Fonseca; Renzo Pradel; Edgardo M. Rengifo; Mariela Leo; Víctor Pacheco; Alexandre Aleixo; Alexandre R. Percequillo; Pedro Peloso (Systematics and Biodiversity, 2024)

Corrigendum to “Surviving the Tide: Assessing Guiana dolphin persistence amidst growing threats in a protected estuary in South-eastern Brazil” [J. Nature Conserv. 82 (2024) 126713] - Inaê Guion de Almeida; Alexandre Reis Percequillo; Mario Manoel Rollo (Journal for Nature Conservation, 2024)

Surviving the Tide: Assessing Guiana dolphin persistence amidst growing threats in a protected estuary in South-eastern Brazil - Inaê Guion de Almeida; Alexandre Reis Percequillo; Mario Manoel Rollo (Journal for Nature Conservation, 2024)

Phylogenomics and species delimitation of an abundant and little-studied Amazonian forest spiny rat - Jeronymo Dalapicolla; Joyce Rodrigues do Prado; L. Lacey Knowles; Alexandre Reis Percequillo (Molecular Phylogenetics and Evolution, 2024)

Andean non‐volant small mammals: A dataset of community assemblages of non‐volant small mammals from the high Andes - Edgardo M. Rengifo; Jorge Brito; J. Pablo Jayat; Raisa Cairampoma; Agustina Novillo; Natali Hurtado; Ignacio Ferro; Cesar E. Medina; Alfonso Arguero; Sergio Solari; Jose Urquizo; Ariatna Villarreal; et al. (Ecology, 2022)
Information from diversity inventories was used to study patterns of biodiversity and species distribution, to identify potential priority areas for conservation, and to guide future sampling efforts. In this context, we compiled information on non‐volant small mammal communities from the high Andes (>2000 m). Here, we present an open source dataset containing information on diversity (species composition, number of individuals captured), inventory design (type of traps, sampling efforts), and environment (habitat) for both unpublished and published information. This study covers 630 mammalian communities, geographically distributed throughout the Andes in Venezuela, Colombia, Ecuador, Peru, Bolivia, Argentina, and Chile. We compiled a total of 26,412 individual records belonging to 240 species; the order with greatest number of records was Rodentia ( n = 25,319, 96.06%), followed by Didelphimorphia ( n = 373, 1.42%), Eulipotyphla ( n = 358, 1.36%) and Paucituberculata, ( n = 307, 1.16%). Andean non‐volant small mammal communities harbor a range from 1 to 17 species, with 93.06% of sites being composed of one to five species, 27.78% of sites with species richness varying from 6 to 10 species, and 4.17% sites composed of more than 10 species. Multiple sampling methods were used to survey non‐volant small mammals; the most representative methods were snap‐traps and Sherman traps, or a combination of both, in more than 81% of the studies. This data paper represents the first large dataset of faunal species inventories for the Andes. There are no copyright restrictions associated with the use of this dataset. Please cite this data paper when its data are used total or partially in research or teaching.

Chromosomal evolution of tribe Oryzomyini (Rodentia: Cricetidae: Sigmodontinae) - Camila do Nascimento Moreira; Alexandre Reis Percequillo; Malcolm Andrew Ferguson-Smith; Yatiyo Yonenaga-Yassuda; Karen Ventura (Mammalian Biology, 2022)

Functional connectivity in sympatric spiny rats reflects different dimensions of Amazonian forest‐association - Jeronymo Dalapicolla; Joyce Rodrigues do Prado; Alexandre Reis Percequillo; L. Lacey Knowles (Journal of Biogeography, 2021)
Aim Understanding how the landscape influences gene flow is important in explaining biodiversity, especially when co‐distributed taxa across heterogeneous landscapes exhibit species‐specific habitat associations. Here, we test predictions about the effects of forest‐type on population connectivity in two sympatric species of spiny rats that differ in their forest associations. Specifically, we evaluate the hypothesis that seasonal floodplain forests ( várzea ) provide linear connectivity, facilitating gene flow among individuals, while non‐flooded forests ( terra‐firme ) may diminish the functional connectivity. Location Western Amazon, South America. Taxon Proechimys simonsi (non‐flooded forests, terra‐firme ) and Proechimys steerei (seasonal floodplain forests, várzea ). Methods We analyse about 13,000 single nucleotide polymorphisms along with characterizations of landscape heterogeneity for two forest types to test for differences in the functional connectivity. Influence of the landscape and environmental variables are quantified using maximum‐likelihood population effect models to identify the relative importance of variables in explaining the gene flow. Results There are significant differences in functional connectivity between species. However, the genomic data does not support the conventional hypotheses of higher connectivity for inhabitants of várzea than those of terra‐firme . Stronger genetic structure in P. steerei than P. simonsi based on isolation by distance models suggests reduced gene flow in species associated with várzea forests. Isolation by resistance reinforces that wetland habitats inhibit and promote the functional connectivity in P. simonsi and P. steerei , respectively, although large distances along the rivers can prevent gene flow in P. steerei . Main conclusion Interpreting differences between connectivity in taxa apparent from genetic analyses through the lens of a single dimension of Amazonian heterogeneity—that is, forest type—may be an oversimplification. Our statistical modelling and fit of the data to different models points to specific environmental and habitat differences between the ecological divergent spiny rat species that may contribute to differences in the genetic structure of these sympatric taxa.

Systematics of Brucepattersonius Hershkovitz, 1998 (Rodentia, Sigmodontinae): molecular species delimitation and morphological analyses suggest an overestimation in species diversity - Edson Fiedler Abreu; Diego Marques Henriques Jung; Alexandre Uarth Christoff; Victor Hugo Valiati; Sharon A. Jansa; Alexandre Reis Percequillo (Systematics and Biodiversity, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Bottom-up effect: a rodent outbreak following the bamboo blooming in a Neotropical rainforest - Ricardo Siqueira Bovendorp; Neander Marcel Heming; Alexandre Reis Percequillo (Mammal Research, 2020)

Unraveling Deep Branches of the Sigmodontinae Tree (Rodentia: Cricetidae) in Eastern South America - Pablo R. Gonçalves; Alexandre U. Christoff; Leonardo F. Machado; Cibele R. Bonvicino; Felipe B. Peters; Alexandre R. Percequillo (Journal of Mammalian Evolution, 2020)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Similar but different: Revealing the relative roles of species‐traits versus biome properties structuring genetic variation in South American marsh rats - Joyce R. Prado; Alexandre R. Percequillo; Andréa T. Thomaz; L. Lacey Knowles (Journal of Biogeography, 2019)
Aim Wetland habitats, and the ecological restrictions imposed by them, structure patterns of genetic variation in constituent taxa. As such, genetic variation may reflect properties of the specific biomes species inhabit, or shared life history traits among species may result in similar genetic structure. We evaluated these hypotheses jointly by quantifying the similarity of genetic structure in three South American marsh rat species ( Holochilus ), and test how genetic variation in each species relates to biome‐specific environmental space and historical stability. Location South America. Taxon Rodentia. Methods Using complementary analyses (Mantel tests, db RDA , Procrustes, covariance structure of allele frequencies and environmental niche models [ ENM s]) with 8,000–32,000 SNP s per species, we quantified the association between genomic variation and geographic and/or environmental differences. Results Significant association between genetic variation and geography was identified for all species. Similarity in the strength of the association suggests connectivity patterns dictated by shared species‐traits predominate at the biome scale. However, substantial amounts of genetic variation are not explained by geography. Focusing on this portion of the variance, we demonstrate a significant quantitative association between genetic variation and the environmental space of a biome, and a qualitative association with varying regional stability. Specifically, historically stable areas estimated from ecological niche models are correlated with local levels of geographic structuring, suggesting that local biome‐specific histories affect population isolation/connectivity. Main conclusions These tests show that although species exhibit similar patterns of genetic variation that are consistent with shared natural histories, irrespective of inhabiting different wetland biomes, local biome‐specific properties (i.e. varying environmental conditions and historical stability) contribute to departures from equilibrium patterns of genetic variation expected by isolation by geographic distance. The reflection of these biome‐specific properties in the genetic structure of the marsh rats provides a window into the differences among South American wetlands with evolutionary consequences for their respective constituent assemblages.

CERRADO SMALL MAMMALS: abundance and distribution of marsupials, lagomorphs, and rodents in a Neotropical savanna - André Mendonça; Alexandre R. Percequillo; Nicholas F. Camargo; Juliana F. Ribeiro; Alexandre R. T. Palma; Leonardo C. Oliveira; Edeltrudes M. V. C. Câmara; Emerson M. Vieira (Ecology, 2018)
Patterns in distribution and local abundance of species within a biome are central concerns in ecology and allow the understanding of the effects of habitat loss on rates of species extinction; provide support for the creation and management of reserves; and contribute to the identification and quantification of the processes that allow niche partitioning by species. However, despite the importance in the conservation and management of the ecosystems, most systematized information on the abundance and distribution of small mammals is restricted to the northern hemisphere or forest ecosystems. For tropical biomes, an important part of this information remains dispersed and difficult to access in the form of theses, technical reports, or unpublished data sets. Here we present a comprehensive data set of abundance and richness of small mammals in the Cerrado, the largest Neotropical savanna. This data set includes 2,599 records of 446 sites from 96 studies. More than 50% of references in this data set are peer‐reviewed journal articles, but 45.78% of communities were compiled from theses. The data set comprises 24,283 individuals of 55 genera and at least 118 species of small mammals including 29 marsupials, two lagomorphs (one exotic), and 87 rodents (three exotic). Local species richness ranged from 1 to 26 species (5.82 ± 3.55, average species richness ± SD ). We observed hyperdominance of a few species; the 10 most abundant species in this data set represented 60.19% of all recorded individuals. The hairy‐tailed bolo mouse ( Necromys lasiurus ) represented over than 20% of all individuals and occurred at more than 50% of sites. Furthermore, we identified 18 environments, 16 native vegetation types, and 2 anthropic environments. Typical savanna and gallery forest were the most frequently sampled vegetation types (comprising 46.94% of all sampled sites) and the most speciose ones (57 species for typical savanna and 53 species for gallery forest). The information contained in this data set can be used to analyze ecological questions such as the relationship between local abundance and regional distribution, the relevance of local and regional factors to community structuring, and the role of phylogenetic mechanisms in community assemblage. It can also be useful in conservation efforts in this biodiversity hotspot. No copyright, proprietary, or cost restrictions apply. Please cite this paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Systematic Studies of the Genus Aegialomys Weksler et al., 2006 (Rodentia: Cricetidae: Sigmodontinae): Geographic Variation, Species Delimitation, and Biogeography - Joyce Rodrigues do Prado; Alexandre Reis Percequillo (Journal of Mammalian Evolution, 2018)

ATLANTIC MAMMAL TRAITS : a data set of morphological traits of mammals in the Atlantic Forest of South America - Fernando Gonçalves; Ricardo S. Bovendorp; Gabrielle Beca; Carolina Bello; Raul Costa‐Pereira; Renata L. Muylaert; Raisa R. Rodarte; Nacho Villar; Rafael Souza; Maurício E. Graipel; Jorge J. Cherem; Deborah Faria; et al. (Ecology, 2018)
Measures of traits are the basis of functional biological diversity. Numerous works consider mean species‐level measures of traits while ignoring individual variance within species. However, there is a large amount of variation within species and it is increasingly apparent that it is important to consider trait variation not only between species, but also within species. Mammals are an interesting group for investigating trait‐based approaches because they play diverse and important ecological functions (e.g., pollination, seed dispersal, predation, grazing) that are correlated with functional traits. Here we compile a data set comprising morphological and life history information of 279 mammal species from 39,850 individuals of 388 populations ranging from −5.83 to −29.75 decimal degrees of latitude and −34.82 to −56.73 decimal degrees of longitude in the Atlantic forest of South America. We present trait information from 16,840 individuals of 181 species of non‐volant mammals (Rodentia, Didelphimorphia, Carnivora, Primates, Cingulata, Artiodactyla, Pilosa, Lagomorpha, Perissodactyla) and from 23,010 individuals of 98 species of volant mammals (Chiroptera). The traits reported include body mass, age, sex, reproductive stage, as well as the geographic coordinates of sampling for all taxa. Moreover, we gathered information on forearm length for bats and body length and tail length for rodents and marsupials. No copyright restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Atlantic small‐mammal: a dataset of communities of rodents and marsupials of the Atlantic forests of South America - Ricardo S. Bovendorp; Nacho Villar; Edson F. de Abreu‐Junior; Carolina Bello; André L. Regolin; Alexandre R. Percequillo; Mauro Galetti (Ecology, 2017)
The contribution of small mammal ecology to the understanding of macroecological patterns of biodiversity, population dynamics, and community assembly has been hindered by the absence of large datasets of small mammal communities from tropical regions. Here we compile the largest dataset of inventories of small mammal communities for the Neotropical region. The dataset reviews small mammal communities from the Atlantic forest of South America, one of the regions with the highest diversity of small mammals and a global biodiversity hotspot, though currently covering less than 12% of its original area due to anthropogenic pressures. The dataset comprises 136 references from 300 locations covering seven vegetation types of tropical and subtropical Atlantic forests of South America, and presents data on species composition, richness, and relative abundance (captures/trap‐nights). One paper was published more than 70 yr ago, but 80% of them were published after 2000. The dataset comprises 53,518 individuals of 124 species of small mammals, including 30 species of marsupials and 94 species of rodents. Species richness averaged 8.2 species (1–21) per site. Only two species occurred in more than 50% of the sites (the common opossum, Didelphis aurita and black‐footed pigmy rice rat Oligoryzomys nigripes ). Mean species abundance varied 430‐fold, from 4.3 to 0.01 individuals/trap‐night. The dataset also revealed a hyper‐dominance of 22 species that comprised 78.29% of all individuals captured, with only seven species representing 44% of all captures. The information contained on this dataset can be applied in the study of macroecological patterns of biodiversity, communities, and populations, but also to evaluate the ecological consequences of fragmentation and defaunation, and predict disease outbreaks, trophic interactions and community dynamics in this biodiversity hotspot.

Connectivity maintain mammal assemblages functional diversity within agricultural and fragmented landscapes - Marcelo Magioli; Katia Maria Paschoaletto Micchi de Ferraz; Eleonore Zulnara Freire Setz; Alexandre Reis Percequillo; Michelle Viviane de Sá Santos Rondon; Vanessa Villanova Kuhnen; Mariana Cristina da Silva Canhoto; Karen Evelyn Almeida dos Santos; Claudia Zukeran Kanda; Gabriela de Lima Fregonezi; Helena Alves do Prado; Mitra Katherina Ferreira; et al. (European Journal of Wildlife Research, 2016)

Ticks (Acari: Ixodidae) identified from prey–predator interactions via faecal analysis of Brazilian wild carnivores - Thiago F. Martins; Thaís R. Diniz-Reis; Gustavo S. Libardi; Alexandre R. Percequillo; Luciano M. Verdade; Eliana R. Matushima; Marcelo B. Labruna (Experimental and Applied Acarology, 2015)

Species richness and areas of endemism of oryzomyine rodents (Cricetidae, Sigmodontinae) in South America: an ndm / vndm approach - Joyce R. do Prado; Pamella G. G. Brennand; Leandro P. Godoy; Gustavo S. Libardi; Edson F. de Abreu‐Júnior; Paulo R. O. Roth; Elisandra A. Chiquito; Alexandre R. Percequillo (Journal of Biogeography, 2015)
Aim To infer areas of endemism for the tribe Oryzomyini in South America by employing a database of species richness and geographical distribution, and to compare these results with areas of endemism and species richness proposed in the literature for other taxa. Location We analysed specimens of the tribe Oryzomyini distributed throughout South and Central America, which are housed in European, North and South American museums and collections. Methods We analysed 2768 occurrence records for 102 species of the tribe Oryzomyini using the ndm / vndm algorithm and three different grid sizes to assess the possible effects of grid cell area on the results. Results Using the overlap of consensus areas in South America, we identified three generalized areas of endemism for the Oryzomyini: north‐western South America ( NWSA ), eastern South American ( ESA ), and northern South America ( NSA ); we also identified the Galápagos archipelago ( GA ) as an area of endemism. Main conclusions Areas of endemism detected in the continental portion of South America include its three main mountain chains: the Andes Cordillera, the Guyanan Shields, and an area east of the Brazilian Shield named Serra do Mar. Each of these regions encompasses many different types of vegetation, and the species richness and composition of the areas of endemism of the tribe are directly related to this environmental diversity. Different grid sizes affected the distributional heterogeneity of the consensus areas. The smallest grid cell size identified mainly Andean areas, which contain a higher number of more exclusive species in a small area along a steep elevational gradient. In contrast, the largest grid size identified areas of endemism along an environmental gradient that co‐varied with latitude and longitude. The identified areas of endemism are corroborated by previous studies on other taxa.